Participação de crianças nas rotinas da educação infantil - Almeida, Synara do Espírito Santo (2015)
It is a qualitative research, based on a case study, which aimed to understand what aspects of the school context interfere in the ways of social participation of children in the routines of early childhood education in a municipal school in the city of Estância/SE. Survey participants were 21, 05 years old, children of both sexes (12 girls and 09 boys) and 07 women. The materials used for the production of data was A4 paper, colored pencils, crayons and play dough, plus the following instruments: camera, notebook for field notes, audio recorder, audio recorder with computer, script observation and semi-structured interviews. Two semi-structured dating activities with children and three meetings of Focus Group with teachers were conducted. The data obtained from the field diary, transcripts of audios and drawings produced by children were analyzed, resulting in the following categories: (1) Disciplining; (2) Schooling; (3) Routinization; (4) Interaction; (5) Motivation; (6) Toys / games and (7) Environment. That done, drawings, photos and excerpts of transcripts or observations were separated to demonstrate aspects of the school environment that interfered in the ways of social participation of the children in school routines. Sought to triangulation of the data for presentation and understanding of the results. The results showed that disciplining managing early childhood education, with arbitrary rules, without meaning to children disrupted the interaction among peers and the teacher-child interaction. The schedules of institutional routine were not articulated thinking about the needs and different rhythms of learning of the children; environmental organization was not part of the routine; there is a lack of a space for the discussion and reflection of teaching practices between teachers working in the school; lack of family and community participation in the activities and planning of the educational institution; lack of training courses for teachers intended on expanding and updating their knowledge on child-rearing practices. Therefore believed to be essential to review the pedagogical practices, the environment and school routine. Also, make municipal level changes to meet the need of continuous formation of the school personnel, obtain the effective participation of the family and community in the educational institution, the appreciation and recognition of the teacher as the child's learning mediator. These aspects can be modified to be attuned to the needs and interests of children, making pedagogical practices undestanding for them.